75 Years : the very best of Life - Sullivan, Robert, 1953- (Life Books, 2011)
Presents a selection of the best photographs published in "Life" magazine and by Life Books, including war pictures, candid shots of celebrities, nature scenes, and views of social and cultural concerns, along with a facsimile of the first issue.